Answer:
(b - c)(a - d)
Step-by-step explanation:
Given
a(b - c) + d(c - b) ← factor out - 1
= a(b - c) - d(b - c) ← factor out (b - c) from each term
= (b - c)(a - d)
Answer:
1. A. ![4.42](https://tex.z-dn.net/?f=4.42)
2. F. ![20.9](https://tex.z-dn.net/?f=20.9)
3. G. ![4.57](https://tex.z-dn.net/?f=4.57)
4. A. ![4.50](https://tex.z-dn.net/?f=4.50)
Step-by-step explanation:
Answer:
Please the attached file for the answer. I hope that helps
Answer:
4
Step-by-step explanation:
Since the line of the function is passing through the point (3, 4).
Here x = 3 and y = 4
So the value of the function at x=3 is 4.